Anabaptism is Neither Catholic nor Protestant - Constantine PROKHOROV (Богословські роздуми: Східноєвропейський журнал богословʼя)
The author of the paper shows the weakness of the traditional understanding of Anabaptism of the sixteenth century as a kind of Protestantism. There are a number of important arguments to prove the position that, in reality, Anabaptism was the “third way” movement. The Anabaptists were not Catholics because they outwardly looked like the Protestants, proclaiming the Reformed principle of sola Scriptura, and denying all the complicated Roman Catholic rites, hierarchy, and sacred objects. At the same time, the Anabaptists were not Protestants because they in wardly retained the Catholic mentality, defending things such as the freedom of the will, rejecting double predestination, asserting anecclesiocentric theology, keeping the main monastic values, using a strict system of discipline, and struggling against state control. Anabaptism was a unique phenomenon, however, having deep roots in the medieval Christian tradition.